Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics

Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics